2009
DOI: 10.1002/pssb.200945144
|View full text |Cite
|
Sign up to set email alerts
|

In rich In1−x Ga x N: Composition dependence of longitudinal optical phonon energy

Abstract: The composition dependence of longitudinal optical (LO) phonon energies in undoped and Mg-doped In 1Àx Ga x N samples are determined using Raman spectroscopy in the range of Ga fraction from x ¼ 0 to x ¼ 56%. The LO phonon energy varies from 73 meV for InN to 83 meV for In 1Àx Ga x N with 56% Ga.Independent measurements of temperature dependent mobility at high temperatures where LO phonon scattering dominates the transport were also used to obtain the LO phonon energy for x ¼ 0 and x ¼ 20%. The results obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…At high temperatures polar optical phonon scattering is the dominant scattering mechanism in GaN [19]. The LO phonon scattering limited mobility (μ LO ) can be extracted from the measured Hall mobility by rewriting Matthiessen's rule [33] as…”
Section: Resultsmentioning
confidence: 99%
“…At high temperatures polar optical phonon scattering is the dominant scattering mechanism in GaN [19]. The LO phonon scattering limited mobility (μ LO ) can be extracted from the measured Hall mobility by rewriting Matthiessen's rule [33] as…”
Section: Resultsmentioning
confidence: 99%
“…3 for a review on III-V alloys). Numerous studies have been devoted to study the vibrational properties of hexagonal InGaN thin films [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and InGaN/GaN quantum wells. [22][23][24] Although it is well accepted that both the A 1 (LO) and the E 2h phonon modes of InGaN display a one-mode behavior, 15,16 there are still open questions regarding the behavior of the optical phonons in the InGaN alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Such deviations are usually attributed to the strain of the samples. 12,20 However, many authors have shown that the A 1 (LO) frequency strongly depends on the excitation wavelength and/or on temperature, and different effects have been invoked to explain the observations: i) strain and/or compositional gradients over depth; 13,19 ii) compositional inhomogeneities giving rise to selective resonant excitation of domains with a particular In content; 5,7,15,17 iii) relaxation of the wave-vector selection rule. 18 Thus, it remains necessary to identify which mechanisms are actually playing a key role in the behavior of the A 1 (LO) mode of InGaN.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of Ga x In 1Àx N layer were estimated from growth parameters and verified by Rutherford backscattering spectrometry as 500 nm. 11 Since the critical thickness of Ga x In 1Àx N alloys (0 < x < 0.56) is less than 10 nm, 12,13 we may assume that Ga x In 1Àx N alloys are fully relaxed. The free carrier concentrations were obtained from Hall Effect measurements.…”
Section: Methodsmentioning
confidence: 99%